Serologic biomarkers for acute mesenteric ischemic: a systematic review - Ting-Yu CHEN; Yi-Fan ZHAO; Chao ZHANG; Guo-Xiang TIAN (Yixue xinzhi zazhi)
Objective To evaluate the effects of classical markers, novel serological biomarkers and other markers on the diagnosis of acute mesenteric ischemia (AMI).Methods PubMed and Embase were searched by computer to collect and evaluate the studies on serum markers of AMI from the estab-lishment of the database to August 15, 2020. Qualitative induction was conducted for the included studies.Results A total of 28 studies, including 5 meta-analysis, 7 prospective studies, 8 retrospective studies, 4 cross-sectional studies and 4 animal studies, were included. The speciality and sensitivity of classic markers (L-lactic acid, D-lactic acid and LDH) were low. The new serological biomarkers (D-dimer, platelet index, neutrophil-lymphocyte ratio, ischemia modifies albumin, 1-fatty acid binding protein, a-glutathione s-transferase, citruline) and other markers of AMI can be improved to some ex-tent, but the diagnostic value is still relatively limited.Conclusion The diagnostic value of serum bi-omarkers of AMI is limited, and it is still difficult for those markers to be used to diagnose AMI in differ-ent types and stages. High-quality and large-sample studies are still needed to confirm it.